2006
DOI: 10.1021/ja0553856
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Energy Landscape of a Small RNA Hairpin

Abstract: The energy landscape of a small RNA tetraloop hairpin is explored by temperature jump kinetics and base-substitution. The folding kinetics are single-exponential near the folding transition midpoint T(m). An additional fast phase appears below the midpoint, and an additional slow phase appears above the midpoint. Stem mutation affects the high-temperature phase, while loop mutation affects the low-temperature phase. An adjusted 2-D lattice model reproduces the temperature-dependent phases, although it oversimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
233
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(253 citation statements)
references
References 32 publications
20
233
0
Order By: Relevance
“…The ruggedness of the folding free-energy landscapes of nucleic acid hairpins has been explored in several experiments using temperature jump methods to monitor kinetic transitions away from the melting temperature (10,20,45). Based on rates of refolding, these studies identified ensembles of partially stacked structures in submelting regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ruggedness of the folding free-energy landscapes of nucleic acid hairpins has been explored in several experiments using temperature jump methods to monitor kinetic transitions away from the melting temperature (10,20,45). Based on rates of refolding, these studies identified ensembles of partially stacked structures in submelting regions.…”
Section: Discussionmentioning
confidence: 99%
“…These tetraloop structures have been explored through multiple experimental (16)(17)(18)(19)(20)(21)(22)(23) and computational (24)(25)(26)(27) analyses that have revealed important clues about RNA thermodynamic stability and relate to the processes that govern the formation and stabilization of basic RNA molecules. Many tetraloops containing the conserved nucleotide sequence GNRA (N = A,C, G,U; R = A,G) possess an inherent global flexibility that manifests through multiple configurational states (19,21,22,28).…”
mentioning
confidence: 99%
“…23,33,34 The number of experimentally determined high resolution RNA structures 30,31,35 continues to increase, enabling us to understand the interactions that stabilize the folded states. Single molecule [36][37][38][39][40][41] and ensemble experiments [42][43][44] using a variety of biophysical methods combined with theoretical techniques 14,34 have led to a conceptual framework for predicting various mechanisms by which RNA molecules fold. In order to make further progress new computational tools are required.…”
Section: Introductionmentioning
confidence: 99%
“…Hairpins are a fundamental RNA secondary structure motif (33) and perform many biologically relevant functions, but our understanding of their folding is still incomplete (34)(35)(36)(37)(38). The folding of this hairpin is diffusion controlled (37,39,40), so despite its small size, the folding time is on the microsecond time scale, as measured by laser temperature jump experiments (35). Thus, capturing a single folding event with a single MD simulation with explicit solvent would likely take more than a year on a typical CPU.…”
mentioning
confidence: 99%